Mediation Model Of Job Satisfaction In The Relationship Between Digital Competence, Work Motivation, And The Performance Of Civil Servants - Rima Santy; Djatmiko Noviantoro; Nasir (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study aims to analyse the effect of digital competence and work motivation on the performance of Civil Servants (ASN) with job satisfaction as a mediating variable at the Regional Secretariat of South Sumatra Province. The study uses a quantitative approach with an explanatory design. The research sample consisted of 85 ASNs selected through stratified random sampling from a total population of 553 employees. Data analysis was performed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with the assistance of SmartPLS 4. The results showed that digital competence and work motivation had a positive and significant effect on job satisfaction (β=0.342; p<0.001 and β=0.428; p<0.001). Digital competence and work motivation also have a significant effect on civil servant performance (β=0.246; p=0.007 and β=0.287; p=0.002). Job satisfaction was found to have a significant effect on civil servant performance (β=0.445; p<0.001) and partially mediated the relationship between digital competence and work motivation on performance. The research model showed strong predictive power with an R² value of 0.871 for job satisfaction and 0.724 for civil servant performance. These findings confirm that improving digital competence and work motivation must be integrated with strategies to increase job satisfaction in order to encourage optimal civil servant performance in the era of digital transformation in government